Emergency general surgery and trauma: Outcomes from the first consultant-led service in Singapore. Issue 1 (January 2018) - Mathur, Sachin; Lim, Woan Wui; Goo, Tiong Thye
Abstract: Introduction: There is a significant burden on public health systems from emergency surgical and trauma (ESAT) patients. In Western countries, the response has been to separate acute and elective surgery with the creation of a new sub-specialty: acute care surgery. Dedicated acute units have shown improvements in efficiency and clinical outcomes for patients. The aim of this study was to assess the results of the first such unit in Singapore. Materials and methods: A retrospective analysis was performed of a 12-month period of acute admissions between May 2014 and April 2015, with comparison of 6-months before and after the creation of the ESAT service. The ESAT service was a consultant led dedicated team managing all daily acute and trauma patients. Demographic, efficiency and clinical outcome key performance indicators were compared. Results: There were 2527 acute admissions split between the two time periods. The ESAT service (N = 1279) managed soft tissue infections (257, 20%), appendicitis (199, 16%) and biliary disease (175, 14%) most commonly. The most common of the 573 procedures performed were incision and drainage (242, 42%), appendicectomy (188, 33%) and laparotomy (84, 16%). Clinical outcome during the ESAT service included reduction in overall mean length of stay (4.5d to 3.5d, P < 0.01) and mortality (24/1248 (1.9%) to 11/1279 (0.9%), P = 0.03). Efficiency gains in theatre booking time, ED surgical review and overall costs were also noted. Conclusion: The creation of an ESAT service has led to improved efficiency of care with no worsening of clinical outcomes for acute general surgical and trauma patients.